Awareness and Usage of ICT-Based Library and Information Servicesamong the Library Users of Vivekanand Central Library of Central University of Jharkhand, Ranchi: A Case Study (LIS TODAY, 2025)
This study investigates the awareness, usage, and satisfaction levels of ICT-based  library and information services among users of Vivekanand Central Library, Central  University of Jharkhand, Ranchi. Using a structured questionnaire distributed to  125 participants, with a 91.20% response rate, the research explores demographic  insights, frequency of library visits, primary purposes for access to library services,  and satisfaction levels. The relevant data was analysed using SPSS statistical analysis  software. Further, mean, standard deviation and simple percentage were calculated  for different variables. Key findings reveal a preference for print resources over  electronic formats, with RFID-based automated issue-return being the most  utilized ICT service. Challenges like low Internet connectivity and unawareness of  available resources were identified, alongside moderate satisfaction levels with ICT based services. Recommendations include improving internet access, expanding  ICT training sessions, and enriching the library’s digital collections to serve user  needs better. This case study underscores the evolving role of academic libraries in  integrating technology to enhance user engagement and accessibility.
Keywords: Academic Library; Information Access; Information Communication Technology; Library Services; Library Usage; User Study